Through the gates of the silver key - Lovecraft, H. P. (Howard Phillips), 1890-1937; Price, E. Hoffmann, 1898-1988 (Salt Lake City, UT : Project Gutenberg, 2023)
"Through the Gates of the Silver Key" by H. P. Lovecraft and E. Hoffmann Price is a short story written between October 1932 and April 1933. This cosmic horror tale follows the mysterious fate of Randolph Carter, who vanished after using a mystical artifact. A robed swami recounts Carter's journey beyond spacetime, where he encounters ancient beings and confronts the ultimate nature of existence itself. His wish to explore an alien consciousness on a distant world leads to catastrophic consequences, trapping him in an unimaginable predicament that transcends human comprehension. (This is an automatically generated summary.)
Wikipedia page on this work: https://en.wikipedia.org/wiki/Through_the_Gates_of_the_Silver_Key
Release date is 2023-07-11
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Fantasy fiction; Horror tales; Paranormal fiction